The Influence of Corporate Social Responsibility on The Corporate Image Of Pt Meares Soputan Mining in The Perception of The Ring 1 Batuputih Community - Anggelia Arni Alda Dahabang; Christien A. Karambut; Vincentius Pantow (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
Corporate Social Responsibility (CSR) has increasingly become a strategic tool for mining companies to build and sustain positive relationships with surrounding communities. This study aims to examine the influence of CSR implementation on the corporate image of PT Meares Soputan Mining (PT MSM) as perceived by the Ring 1 Batuputih Community in Bitung City, North Sulawesi, Indonesia. A quantitative approach was employed using simple linear regression analysis with a sample of 50 respondents drawn from the Ring 1 Batuputih Community. CSR was measured using Carroll’s Triple Bottom Line framework (Economy, Social, and Environment dimensions), while corporate image was assessed through four dimensions: Corporate Personality, Corporate Reputation, Corporate Values, and Corporate Identity. The results indicate that CSR has a positive and significant influence on corporate image (t-test result significant at α = 0.05), with a coefficient of determination (R²) of 0.805, meaning CSR accounts for 80.5% of the variation in corporate image formation. The descriptive analysis revealed that community perception of CSR implementation received a mean score of 3.94 (Good category), while corporate image received a mean score of 3.96 (Good category). Despite generally positive perceptions, areas such as skills training, community involvement in CSR program planning, and environmental transparency were identified as needing improvement. These findings confirm that effective CSR implementation is a key determinant of positive corporate image in the mining sector, particularly in communities directly affected by operational activities.